Deskripsi Kemampuan Literasi Digital Mahasiswa PPG Prajabatan Program Studi PGSD: Penelitian - Aldoni; Hairida; Halidjah; Siti; Kresnadi; Hery; Firmansyah; Andang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the digital literacy level of Pre-Service PPG students of the PGSD Study Program Wave 1 of 2024. The method used is quantitative descriptive with a sample of 25% of students and data obtained from a questionnaire containing 26 statements about 8 components of digital literacy. The results of the study show an overall digital literacy level of 82.11% (good category), with 23.33% of students being very good, 73.33% being good, and 3.33% being sufficient. By component, the percentages include: Functional Skill and Beyond (81.94%), Creativity (77.16%), Collaboration (82.77%), Communication (85.83%), The Ability to Find and Select Information (88.05%), Critical Thinking and Evaluation (76.11%), Cultural and Social Understanding (85%), and E-Safety (84.44%). All components are in the good category.